Opini Publik Tentang Kenaikan Iuran BPJS Kesehatan. (Studi Deskriptif Opini Mahasiswa Universitas Sumatera Selatan) - Erik Asmara; Herdiansyah Amanu; Lovia Evanne (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2021)
BPJS Kesehatan is a program that must be followed by all Indonesian citizens. The government, through Presidential Regulation Number 64 of 2020, has increased the amount of BPJS Health contributions and will take effect from July 1, 2020. The government's efforts to increase the fees have received various responses from the public. Moreover, the government's decision to increase the premium in the conditions of the Covid-19 pandemic. This research was conducted to determine public opinion on the increase in BPJS Health contributions. Also to find out what health services the public expects for BPJS Kesehatan participants. This study uses qualitative methods and data collection using interview and observation techniques. The informants in this study were students of the University of South Sumatra. Analysis of the data used in this study using the Miles and Huberman model. In this study, it can be concluded that the majority of the public disagrees with the government's move to increase the BPJS Health premium. Of the 12 informants, 9 stated that they did not agree with the increase in BPJS Health contributions.